Uncommon Presentation of Gastric Heterotopia Manifesting as a Polypoid Mass - Maria Inês Viegas; Luís Elvas; Daniel Brito; Miguel Areia; Susana Alves; Ana Teresa Cadime (GE: Portuguese Journal of Gastroenterology)
Introduction: Gastric heterotopia (GH) is characterized by the presence of differentiated gastric mucosa tissue outside the stomach, with the most common site being the proximal esophagus, known as the inlet patch. Complications have been reported, but polyps are rarely seen. Despite the low incidence of relevant manifestations described, controversies remain regarding the clinical significance of this condition. Case report: A 53-year-old man with heartburn and regurgitation was referred for management of a sessile polyp (Paris 0-Is) in the proximal esophagus, identified during an esophagogastroduodenoscopy. The patient's medical history includes heavy tobacco consumption. Additionally, he was taking esomeprazole at a dose of 40 mg. We repeated upper gastrointestinal endoscopy and observed two areas of pink mucosa in opposite position in the proximal esophagus, suggestive of gastric heterotopia. One of these areas had a polypoid morphology with congestive and friable mucosa, measuring approximately 12 mm. Narrow Band Imaging evaluation demonstrated a preserved glandular and vascular pattern. Anatomopathological assessment of the lesion revealed fragments of gastric-type mucosa, consisting of occasionally poorly oriented foveolar structures, compatible with ulcerated gastric heterotopia. A multidisciplinary approach led us to decide on an expectant strategy due to its probable benign course. Conclusion: Hyperplastic polyps rarely originate from esophageal inlet patches, and to our knowledge, only a few case reports of gastric heterotopia with polypoid morphology exist in the literature. Further research is needed to determine the most appropriate management for these patients.